EFFECTIVENESS OF VIDEO-BASED HEALTH EDUCATION ON ADOLESCENTS’ FIRST AID FOR FOOD POISONING - Rahma Nur Hamidah; Yuni Sufyanti Arief; Kristiawati Kristiawati (International Journal of Patient Safety and Quality, 2025)
Introduction:Foodborne illness remains a major global public health concern, particularly in communal living environments such as Islamic boarding schools, where adolescents study and dine together. Insufficient knowledge and preparedness in providing first aid for food poisoning can increase morbidity and delay treatment. This study aimed to determine the effectiveness of video-based health education in improving adolescents’ knowledge, attitudes, and behaviors related to first aid for food poisoning. Methods: A quasi-experimental pre-test–post-test control group design was conducted among 72 female adolescents aged 16–18 years residing in two Islamic boarding schools. The intervention group received structured video-based health education, while the control group received printed leaflets containing the same educational content. Data were collected using a validated questionnaire measuring knowledge, attitudes, and practices before and after the intervention. Statistical analyses were performed using the Wilcoxon Signed-Rank Test and Mann–Whitney U Test, with a significance level set at p < 0.05. Results: The findings showed significant improvements in knowledge, attitudes, and behaviors in the intervention group following the video-based education (p < 0.001), while no significant changes were observed in the control group. Inter-group comparisons also indicated statistically significant post-test differences in all behavioral domains (p < 0.001).Conclusion: Video-based health education effectively enhanced adolescents’ knowledge, attitudes, and first-aid behaviors related to food poisoning. The integration of audiovisual learning media provides an engaging and efficient approach to strengthen health literacy and emergency response skills among adolescents in school-based health programs.